Sistem Pengelolaan Persedian Obat dengan Metode FEFO di Apotek OPQ - Intan, Tifani; Gunawan, Waliadi; Alif Putra, Tubagus Tyan; Hidayanti, Nur; Kania, Raden; Rudianto, Rudianto (Jurnal Ilmiah Sains dan Teknologi, 2025)
A pharmacy is a healthcare establishment that serves not just as a drugstore but also provides more intricate pharmaceutical services. A primary challenge in pharmacy management is guaranteeing the presence of safe medications and managing drugs approaching their expiration date. Apotek Via Farma is presently struggling with managing its medication inventory, especially in tracking and distributing drugs nearing their expiration date. The existing manual management system raises the likelihood of mistakes and lessens the pharmacy's operational effectiveness. This study intends to establish a drug inventory management system utilizing the FEFO (First Expired First Out) approach at Apotek Via Farma to tackle this problem. The FEFO approach prioritizes the distribution of medications that are nearing their expiration dates. Earlier research has demonstrated that this approach is successful in minimizing losses from expired medications and enhancing service quality.